Analisis Pendapatan Usahatani Padi Di Desa Teppo 1 Kecamatan Patampanua Kabupaten Pinrang - Hidayah, Azhaliyatul; Sheyoputri, Aylee Christine Alamsyah; Salam, Suryawati (Fakultas Pertanian Universitas Bosowa, 2024)
The rice plant is one of the food ingredients that plays a very important role in the economy, namely as an ingredient to meet the basic needs of the community and as a source of livelihood for the community. Analysis of Rice Farm Income with the aim of knowing how much production costs are incurred and income obtained by rice farmers in Teppo 1 Village, Patampanua District, Pinrang Regency. This research will be conducted from June to July 2023. Samples were taken by 18 farmers. The data analysis method uses quantitative descriptive analysis by calculating production costs, receipts, and farm income. The results of the analysis showed that the total receipts amounted to Rp. 33,575,060ha/m.t. The total production cost incurred amounted to Rp. 11,849,579ha/m.t. The amount of income is obtained from the difference between total revenue and total production costs, so that the income generated in this study amounted to Rp. 21,725,481ha/m.t. Tanaman padi merupakan salah satu bahan pangan yang memegang peranan sangat penting bagi perekonomian yaitu sebagai bahan untuk mencukupi kebutuhan pokok masyarakat maupun sebagai mata pencaharian masyarakat. Analisis pendapatan usahatani padi dengan tujuan untuk mengetahui berapa besar biaya produksi yang dikeluarkan dan pendapatan yang diperoleh petani padi di Desa Teppo 1, Kecamatan Patampanua, Kabupaten Pinrang. Penelitian ini dilaksanakan pada bulan Juni sampai Juli 2023. Sampel diambil sebanyak 18 petani. Metode analisis data menggunakan analisis deskriptif kuantitatif dengan menghitung biaya produksi, penerimaan, serta pendapatan usahatani. Hasil analisis menunjukkan bahwa jumlah penerimaan sebesar Rp.33.575.060/ha/m.t. Total biaya produksi yang dihasikan sebesar Rp.11.849.579/ha/m.t. Besarnya pendapatan diperoleh dari selisih total penerimaan dengan total biaya produksi, sehingga pendapatan yang dihasilkan dalam penelitian ini sebesar Rp.21.725.481/ha/m.t.